2021
DOI: 10.2174/1570162x19666210812113137
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Ocular Complications of Human Immunodeficiency Virus Infection

Abstract: : HIV/AIDS continues to be a major global public health issue, affecting multiple organs such as the eyes. With the advent of highly active antiretroviral therapy (HAART), the incidence has dropped but HIV ocular complications still remain a major cause of vision impairment in HIV-positive individuals. Since modern medical interventions nowadays can change this previously fatal infection into a chronic disease and enable people living with HIV for relatively long and healthy lives, recent studies update the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This has been observed in our previous studies using SIVmac239-infected macaques, where older macaques exhibited rapid development of HIV associated with preinfection immunosenescence characteristics, such as low naive CD4 + T cells and accumulated memory T cells [ 27 , 28 ]. Thirdly, CD4 + T cells in older individuals show elevated levels of immune activation [ 29 ], apoptosis, and depletion [ 30 , 31 ]. Additionally, disorders in secondary lymphoid tissues, dysregulated T-cell subsets, imbalanced cytokine levels, and chronic inflammation may further impede immune recovery in older participants [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in our previous studies using SIVmac239-infected macaques, where older macaques exhibited rapid development of HIV associated with preinfection immunosenescence characteristics, such as low naive CD4 + T cells and accumulated memory T cells [ 27 , 28 ]. Thirdly, CD4 + T cells in older individuals show elevated levels of immune activation [ 29 ], apoptosis, and depletion [ 30 , 31 ]. Additionally, disorders in secondary lymphoid tissues, dysregulated T-cell subsets, imbalanced cytokine levels, and chronic inflammation may further impede immune recovery in older participants [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, noninfectious microvasculopathy resulting from direct invasion of HIV and HIV-associated opportunistic infections are caused by viruses such as cytomegalovirus and varicella zoster virus. 5 In a study of 787 patients with HIV treated with cART in China, we found a high prevalence of ocular complications (26.3%); among them, cytomegalovirus retinitis (CMVR) had the highest prevalence (10.6%), followed by ocular microangiopathy (9.4%). 6 The blood-retinal barrier (BRB) is particularly tight and restrictive and is a physiologic barrier that maintains the eye as a privileged site.…”
Section: Introductionmentioning
confidence: 97%
“…Agglutinin-like sequence protein (Als) family and hyphal-regulated (Hyr/Iff)-like proteins are two of the major proteins which are known for adhesion/invasion of host tissues and evasion of host immune defense, respectively [ 28 , 29 , 30 , 31 ]. The N-terminal of these proteins is predominantly conserved and forms a β-helical structure followed by an α-crystallin domain and shows structural similarities with different bacterial adhesins [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%